Effects of apron length on jet flipping below a sluice gate - Tionardy, Andrew Julius. (2012)
The study is conducted at Nanyang Technological University (NTU) B5 Hydraulic Lab to investigate and have a better understanding on the jet flipping characteristics under varying flow conditions such as the tail-water depth, flow rate and apron length.